Battery storage systems integrated renewable energy sources: A biblio metric analysis towards future directions - Wali S.B.; Hannan M.A.; Reza M.S.; Ker P.J.; Begum R.A.; Rahman M.S.A.; Mansor M. (Elsevier Ltd, 2023)
Electric batteries; Electromagnetic wave emission; Integration; Natural resources; Renewable energy resources; Surveys; Algorithm development; Battery energy storage systems; Battery storage system; Further development; Metric analysis; Re-integration; Renewable energy source; Scopus database; Battery storage